Ground-Motion Simulation in the Lower Tagus Valley Basin - Borges, J.F. (2015)
Throughout history, the Lower Tagus Valley (LTV) region has been shaken by several earthquakes, including some with moderate to large magnitudes and with sources located inside the basin, for example the 1344 (M6.0) and 1909 (M6.0) earth- quakes. Previous simulations (BEZZEGHOUD et al. Natural Hazard 69: 1229–1245, 2011) have revealed strong amplification of the amplitude waves in the region, because of the effect of the low- velocity sediments that fill the basin. The model used in those simulations was updated in this work by including new high- resolution geophysical and geotechnical data available for the area (seismic reflection, aeromagnetic, gravimetric, deep wells, standard penetration tests, and geological data). To contribute to improved assessment of seismic hazard in the LTV, we simulated propaga- tion of seismic waves produced by moderate earthquakes in a 3D heterogeneous medium by using elastic finite-difference wave propagation code. The method, successfully used by GRANDIN et al. (Geophys J Int 171: 1144–1161, 2007), involves evaluation of the seismic potential of known faults in the area studied and three- dimensional seismic ground motion modelling by use of finite difference methods. On the basis of this methodology, we calcu- lated the ground motion for the April 23, 1909, Benavente (Portugal) earthquake (Mw = 6.0) in dense grid points, then computed the synthetic isoseismic map of the area by use of ap- propriate relationships between seismic intensity (MMI) and peak ground velocity (PGV). The synthetic results, in contrast with available macroseismic and instrumental data, enable validation of the source models proposed for the area, identification of the sources of historical earthquakes, and could also indicate which areas are more exposed to seismic ground motion.